Refined Modeling for Power Response Characteristic of Thermal Power Unit under Primary Frequency Control - Kai SHENG; Xin ZOU; Jing QIU; Xiaoxing ZHU (Zhongguo dianli)
Due to the strong-nonlinearity characteristics of the power response of thermal power units, it is difficult to represent the practical power characteristics precisely in terms of the typical linear model. In this paper, through the analysis of the impacts of key factors such as the discharge characteristics of steam turbine valves and throttle pressure on the power response characteristics under primary frequency control, the steam turbine’s valve discharge characteristic and throttle pressure coupling function are introduced as well as the throttle pressure model and the dynamic conversion factor between first stage pressure and load. Then the refined model of power response under primary frequency control is established based on the typical steam turbine model. Finally, the performance of the established model is validated in combination with the primary frequency control test on an actual 660 MW supercritical unit. The results indicate that compared with the typical model, the proposed model demonstrates higher accuracy regarding the power characteristics under primary frequency control.